Diagnostic accuracy of 99mTc-HYNIC-TOC SPECT/CT for detecting osteomalacia-associated tumors - Li, Bo; Duan, Lili; Li, Xiali; Shi, Jingqi; Li, Huiqiang; Liu, Huimin; Cheng, Xiaoliang; Wu, Xinyu; Gao, Yongju (Frontiers in Oncology, 2023)
Objectives: Tumor-induced osteomalacia (TIO) is a rare acquired paraneoplastic disorder characterized by hypophosphatemia resulting from tumor-secreted fibroblast growth factor-23 (FGF23). Surgical resection of the culprit TIO is the first choice of treatment. However, TIO is difficult to detect with conventional diagnostic tools due to its small size and variable location in the body. Somatostatin receptor scintigraphy (SSR) has recently emerged as a functional molecular imaging choice for TIO detection and localization. This research was undertaken to evaluate the efficacy of 99m Tc-labeled hydrazinonicotinyl-Tyr3-octreotide ( 99m Tc-HYNIC-TOC) SPECT/CT in detecting TIO.Methods: 99m Tc-HYNIC-TOC SPECT/CT and the available clinical data of 25 patients with suspected TIO were analyzed retrospectively. The 99m Tc-HYNIC-TOC SPECT/CT findings were compared with the post-surgical pathology diagnosis and clinical follow-up results.Results: Using 99m Tc-HYNIC-TOC SPECT/CT, suspicious tumors were found in 18 of the 25 patients, and 15 of them underwent surgical resection.The post-operative pathology confirmed a TIO in those 13 patients whose symptoms and biochemical anomalies gradually resolved after the surgery.The remaining five patients were finally considered false positives. Moreover, the 99m Tc-HYNIC-TOC SPECT/CT results were negative in seven patients, with six patients being true negative (4 patients were diagnosed with acquired Fanconi syndrome and 2 patients responded well to conservative therapy) and one being false negative. Therefore, the sensitivity and specificity values of 99m Tc-HYNIC-TOC SPECT/CT in the evaluation of TIO were 92.9% (13/14) and 54.5% (6/11), respectively. The overall accuracy of 99m Tc-HYNIC-TOC SPECT/CT for detecting TIO was 76.0% (19/25).The 99m Tc-HYNIC-TOC SPECT/CT is an accurate imaging modality for locating culprit tumors in TIO.